Development of knowledge in records management by using bibliometric analysis on records management journal / Kamarul Azwan Azman, Mohd Nizam Yunus and Hanis Diyana Kamarudin - Azman, Kamarul Azwan; Yunus, Mohd Nizam; Kamarudin, Hanis Diyana (Faculty of Information Management, 2013)
A bibliometric analysis of 235 articles published in Records Management Journal's 15 years of publication, ranging from 1994-2009 was carried out. The range of articles published per volume is between 9 and 17. Most papers (80%) are single authored or 187 authors out of a total of 235 authors. Elizabeth Shepherd, the most prolific author contributed 7 papers. 174 (59.2%) of the authors are geographically affiliated to United Kingdom. The most productive institution/organization is University of Northumbria, United Kingdom with 24 out of 187 authors. Subject analysis indicates that "Systems Design and Implementation" outnumbered other subjects with 15.8% (37) out of total of 235 articles. Most of the cited publications (97.7%) are in English Language. The majority of articles are research papers contributing 78 articles (33.2%).